Mercury in Finfishes and Shellfishes Inhabiting Ennore Estuary, Madras - K.O., Joseph; J.P., Srivastava (Fishery Technology, 2025)
’lhe concentration of mercury in some commercially important tinfishes and shellflshes from Ennore estuary which receives effluent from a chlor-alkali plant, has been measured. The concentration registered ln flnflshes (Chanos chanos and Lisa macrolepis), prawn (Penaeus indicus) and edible oyster (Crassostrea madrasensis) do not pose an imminent threat to the human consumers or to the biota thernselve. The distribution of mecury load exhibited seasonality, the higher values being observed during monsoon period in all the organisms. The mercury level observed in the biota ls oyster > prawn > fintishes ’l`he rnsults lndlmte the suitability of the oyster, C. madrasensis as a sentinel organism for monitoring mercury contamination in estuaries.